Analisis Pengaruh Ekspor, Utang Luar Negeri, FDI dan Kunjungan Wisatawan Mancanegara Terhadap Cadangan Devisa di Indonesia - Anisa Aulia Fiddien; Muhammad Safar Nasir; Nurul Azizah Az Zakiyyah (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2023)
Every country requires foreign exchange reserves to support national development and as a crucial indicator for stabilizing the economy. The purpose of this study is to determine the impact of Exports, Foreign Debt, Foreign Direct Investment (FDI), and Foreign Tourist Arrivals on Foreign Exchange Reserves in Indonesia for the period 1992-2022. The data used in this research consists of secondary data, employing a time series model (ARDL), and utilizing Eviews version 10 software. The dependent variable utilized is Foreign Exchange Reserves, and the independent variables are Exports, Foreign Debt, FDI, and Foreign Tourist Arrivals. The data sources are obtained from Bank Indonesia (BI), the Central Bureau of Statistics (BPS), and the World Bank. The results of the data processing and research reveal that the variables of Exports and Foreign Debt have a positive and significant impact on foreign exchange reserves, whereas FDI and Foreign Tourist Arrivals do not affect Indonesia's foreign exchange reserves in the short term. However, in the long run, the variables that have a positive and significant impact are Exports and Foreign Tourist Arrivals. On the other hand, Foreign Debt and FDI do not influence Indonesia's foreign exchange reserves from 1992 to 2022.